Age-dependent blood pressure elevation is due to increased vascular smooth muscle tone mediated by G-protein signalling - Wirth, Angela; Wang, Shengpeng; Takefuji, Mikito; Tang, Cong; Althoff, Till F.; Schweda, Frank; Wettschureck, Nina; Offermanns, Stefan (Cardiovascular research, 2016)
AbstractAims. Arterial hypertension is a major risk factor for cardiovascular diseases. The kidney and its natriuretic function are in the centre of the prevai
online publish-ahead-of-print 4 November 2015
Gesehen am 02.07.2020